Pengaruh Digital Storytelling terhadap Peningkatan Kemampuan Literasi Siswa Sekolah Dasar: Kajian Literatur (2015-2024) - Aulia, Hayatun Novi; Sari, Fadillah Deswita; Lindawati, Lindawati (Indonesian Journal of Teacher Education, 2024)
This study aims to analyze the effect of digital storytelling on elementary school students’ literacy skills. The method used in this study is a literature review with a descriptive qualitative approach by analyzing 15 relevant scientific articles published within the period of 2015–2024. Data collection was conducted through Google Scholar database searches based on predetermined inclusion criteria, namely articles that discuss digital storytelling, focus on elementary school level, and are accessible in full text. Data analysis was carried out through identification, selection, and synthesis of relevant articles. The results show that digital storytelling has a positive and significant effect on improving literacy skills, including reading, writing, speaking, and listening skills. In addition, the use of digital storytelling also enhances students’ learning motivation, reading interest, and self-confidence. Therefore, digital storytelling can be considered an innovative and effective learning medium to support the improvement of literacy skills in elementary school students in the digital era.